Effect of Emotional Branding and Consumer Satisfaction towards Consumer loyalty on Tokopedia Consumer in Medan - Silalahi, Armando Al Haqqi; Pohan, Vivi Gusrini Rahmadani; Ginting, Eka Danta Jaya (Universitas Medan Area, 2024)
The Goal of this research is to find out the impact of Emotional Branding and Consumer Satisfaction towards Consumer Loyalty on Tokopedia Consumer in Medan City. This research uses quantitative method with multiple regression model. Based on the results of the analysis, it was found that Emotional Branding affects Consumer Loyalty (p<0.001; p<0.005) with a calculated t value greater than the t table value (4.178> 1.970). In addition, the analysis shows that consumer satisfaction also affects customer loyalty (p < 0.001; p < 0.005) with a calculated t value greater than the t table value (9.588> 1.970). Based on the results of this analysis, it can be concluded that Emotional branding has a positive and significant effect on Consumer Loyalty to Tokopedia Consumers in Medan City. The results also concluded that Consumer Satisfaction has a positive and significant effect on Consumer Loyalty. Therefore, Tokopedia need to improve their consumer satisfaction, and improving their marketing strategy using Emotional Branding so that they can grow more loyal consumer in City.